Evaluating Nephrocheck ® as a Predictive Tool for Acute Kidney Injury - Nalesso, Federico; Cattarin, Leda; Gobbi, Laura; Fragasso, Antonio; Garzotto, Francesco; Calò, Lorenzo Arcangelo (International journal of nephrology and renovascular disease, 2020)
Acute kidney injury (AKI) is a common complication in critically ill patients in the intensive settings with increased risks of short- and long-term complications and mortality. AKI is also associated with an increased length of stay in intensive care units (ICU) and worse kidney function recovery at hospital discharge. The management of AKI is one of the major challenges for nephrologists and intensivists overall for its early diagnosis. The current KDIGO criteria used to define AKI include the serum creatinine and urinary output that are neither sensitive nor specific markers of kidney function, since they can be altered only after hours from the kidney injury. In order to allow an early AKI detection, in the last years, several studies focused on the identification of new biomarkers. Among all these markers, urinary insulin-like growth factor-binding protein (IGFBP-7) and tissue inhibitor of metalloproteinase (TIMP-2) have been proven as the best-performing and have been proposed as a predictive tool for the AKI detection in the critical settings in order to perform an early diagnosis. Patients undergoing major surgery, cardiac surgery, those with hemodynamic instability or those with sepsis are believed to be the top priority patient populations for the biomarker test. In this view, the urinary [TIMP-2] x [IGFBP-7] becomes an important tool for the early detection of patients at high risk for AKI and its integration with the local ICU experience has to provide a multidisciplinary management of AKI with the institution of a rapid response team in order to assess patients and customize AKI management.